Cell entry and cAMP imaging of anthrax edema toxin. - Dal Molin, F; Tonello, F; Ladant, D; Zornetta, I; Zamparo, I; Di Benedetto, G; Zaccolo, M; Montecucco, C (2006)
The entry and enzymatic activity of the anthrax edema factor (EF) in different cell types was studied by monitoring EF-induced changes in intracellular cAMP with biochemical and microscopic methods. cAMP was imaged in live cells, transfected with a fluorescence resonance energy transfer biosensor based on the protein kinase A regulatory and catalytic subunits fused to CFP and YFP, respectively. The cAMP biosensor was located either in the cytosol or was membrane-bound owing to the addition of a tag determining its myristoylation/palmitoylation. Real-time imaging of cells expressing the cAMP biosensors provided the time course of EF catalytic activity and an indication of its subcellular localization. Bafilomycin A1, an inhibitor of the vacuolar ATPase proton pump, completely prevented EF activity, even when added long after the toxin. The time course of appearance of the adenylate cyclase activity and of bafilomycin A1 action suggests that EF enters the cytosol from late endosomes. EF remains associated to these compartments and its activity shows a perinuclear localization generating intracellular cAMP concentration gradients from the cell centre to the periphery.